Linfosarcoma de intestino delgado en el niño - Mir del Junco, José M.; Mencia, Luis Felipe; Nodal, Raúl; Martínez Abreu, Edilia; de Juan, René (Revista Cubana de Pediatría, 2022)
Presentación de un caso.